2004
DOI: 10.1037/0894-4105.18.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Decision Making Related to Working Memory Deficits in Individuals With Substance Addictions.

Abstract: This study examined whether individuals with substance dependence (ISDs) show impairments in working memory and whether there is a relationship between their impairments in decision making as measured by the gambling task (GT) paradigm and working memory as measured by a delayed nonmatching to sample (DNMS) task. Using the GT, 11% of healthy control participants and 61% of ISDs opted for choices with high immediate gains in spite of higher future losses. For the ISDs and controls with equal GT impairments, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
321
2
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(362 citation statements)
references
References 64 publications
23
321
2
6
Order By: Relevance
“…These results suggest that the decision-making impairment among binge drinkers did not result from the type of general cognitive intelligence impairment most likely revealed by tests of working memory (i.e., fluid intelligence). This finding agrees with previous reports of asymmetrical dependent relationship between working memory and decision-making (Bechara & Martin, 2004). That is, working memory is not dependent on the intactness of decision making, while decision-making seems to be influenced by the intactness or impairment of working memory.…”
Section: Discussionsupporting
confidence: 83%
“…These results suggest that the decision-making impairment among binge drinkers did not result from the type of general cognitive intelligence impairment most likely revealed by tests of working memory (i.e., fluid intelligence). This finding agrees with previous reports of asymmetrical dependent relationship between working memory and decision-making (Bechara & Martin, 2004). That is, working memory is not dependent on the intactness of decision making, while decision-making seems to be influenced by the intactness or impairment of working memory.…”
Section: Discussionsupporting
confidence: 83%
“…It is generally found that as the task proceeds, normal subjects learn to choose from the 'good' decks and avoid the 'bad' decks (Bechara et al, 1994;Tranel, Bechara, & Damasio, 2000), thus demonstrating a capacity for self-control that involves the (implicit) recognition of long-term winning options. In people with a diversity of disinhibited behaviours such as substance dependencies or pathological gambling, IGT performance is generally poor, however, as these individuals tend to continue choosing from the disadvantageous decks-even when they realize that it compromises their performance on the task in the long run (Bechara & Martin, 2004;Goudriaan, Oosterlaan, De Beurs, & Van den Brink, 2005). Recently, it has also been demonstrated that overweight women (BMI425) perform poorly on the IGT compared to lean individuals (Davis, Levitan, Muglia, Bewell, & Kennedy, 2004), demonstrating the relevance of this approach for understanding failures in the regulation of eating behaviour.…”
Section: Self-controlmentioning
confidence: 99%
“…Lower working memory capacity or reduced deliberation / reflection time when making decisions are associated with impulsive decisions (Finn et al, 2002). Studies show that lower working memory capacity in younger populations is associated with less advantageous, impulsive decision-making (Bechara & Martin, 2004;Finn et al, 2002;Hinson et al, 2003). Furthermore, MRI studies have shown that aging is highly correlated with shrinkage in prefrontal regions such as the lateral prefrontal cortex, the orbitofrontal cortex, and in prefrontal grey and white matter volumes (Raz et al, 2004(Raz et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%